2006
DOI: 10.1007/s00216-006-0819-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of normal colorectal tissue by FT-Raman spectroscopy

Abstract: FT-Raman spectroscopy was employed to study normal human colorectal tissues in vitro with the aim of evaluating the spectral differences of the complex colon mucous in order to establish a characteristic Raman spectrum. The samples were collected from 39 patients, providing 144 spectra for the statistical analysis. The results enable one to establish three well-defined spectroscopic groups of non-altered colorectal tissues that were consistently checked by statistical (clustering) and biological (histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 6 publications
1
70
0
Order By: Relevance
“…However, while pathologists can demonstrate acceptable levels of agreement for the major comparative groups of cancer against negative cases, the division into subgroups of normal, mild pre-cancerous change, severe pre-cancerous change, and cancer has revealed a poorer level of agreement. In this sense, Raman technique would be able to perform quantitative and qualitative analysis, since it shows high sensitivity to small biochemical changes in biological tissues (Andrade et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, while pathologists can demonstrate acceptable levels of agreement for the major comparative groups of cancer against negative cases, the division into subgroups of normal, mild pre-cancerous change, severe pre-cancerous change, and cancer has revealed a poorer level of agreement. In this sense, Raman technique would be able to perform quantitative and qualitative analysis, since it shows high sensitivity to small biochemical changes in biological tissues (Andrade et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However it is essential to assess the accuracy of these techniques so that they may be used as a reliable tool for clinical diagnostics. In that context, it is very important to consider inter-patient variability in regard to both spectral and morphological information [18]. Although previous studies demonstrated very high sensitivity and specificity in tissue discrimination [17], our observations revealed that inter-patient variability may reduce these numbers when implemented for practical applications.…”
Section: Resultsmentioning
confidence: 69%
“…Although previous studies have demonstrated high sensitivities and specificities when discriminating between normal and adenocarcinoma colonic tissues, the Raman spectra obtained in these studies do not show a significantly different fingerprint spectrum in respect to both normal and abnormal tissue. Another crucial factor to be considered would be the occurrence of inter-patient variability in the chemical composition of colonic tissues [18]. Therefore, when considering inter-patient variability [14], the classification efficiency may be lower than the acceptable limits for using Raman spectroscopy alone as a reliable tool for disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This normal mode also involves the exocylic C5-CH 3 group of thymine and is sensitive to the methyl group environment. Adenine also contributes to this intense band (Po et al, 2007). This band shifts to higher frequency side in the presence of Magnesium ion indicating metal binding at N3 atom thymine and adenine.…”
Section: Resultsmentioning
confidence: 89%